Involvement of neurotrophins and their receptors in spondyloarthritis synovitis: relation to inflammation and response to treatment. Issue 11 (7th April 2005) - Rihl, M; Kruithof, E; Barthel, C; De Keyser, F; Veys, E M; Zeidler, H; Yu, D T Y; Kuipers, J G; Baeten, D
Abstract : Objective: To investigate whether expression of the four members of the neurotrophin (NT) family and their four corresponding receptors is related to synovial inflammation in patients with spondyloarthritis (SpA). Material and Methods: Synovial fluid (SF) and serum NTs and their receptors were measured by ELISA. Immunohistochemistry was used for synovial tissue biopsy specimens from patients with SpA, rheumatoid arthritis, and osteoarthritis (OA). In SpA synovium, immunoreactivity of the receptors trkA and NGFRp75 was also assessed before and after 12 weeks of treatment with the monoclonal anti-tumour necrosis factor α antibody, infliximab. Results: mRNA transcripts of all NTs and receptors were expressed in the inflamed synovium. At the protein level, brain derived neurotrophic factor and NT-3 were significantly higher in the SF of patients with SpA than in those with OA. In contrast, ELISA of serum samples showed that the highest member in SpA was NT-4. Immunohistochemistry demonstrated that the NT receptors trkA and NGFRp75 were highly expressed in the inflamed synovium of patients with SpA, correlating with vascularity and lymphoid aggregates, respectively. Additionally, immunoreactivity of both receptors was significantly decreased after infliximab treatment. Conclusions: NTs and their receptors are expressed in inflamed peripheral joints of patients with SpA. Their expression is not constitutive but related to inflammation and they may be involved in the local disease processes.